Nanotechnology in diagnosis and treatment of coronary artery disease. (March 2016) - Karimi, Mahdi; Zare, Hossein; Bakhshian Nik, Amirala; Yazdani, Narges; Hamrang, Mohammad; Mohamed, Elmira; Sahandi Zangabad, Parham; Moosavi Basri, Seyed Masoud; Bakhtiari, Leila; Hamblin, Michael R
Nanotechnology could provide a new complementary approach to treat coronary artery disease (CAD) which is now one of the biggest killers in the Western world. The course of events, which leads to atherosclerosis and CAD, involves many biological factors and cellular disease processes which may be mitigated by therapeutic methods enhanced by nanotechnology. Nanoparticles can provide a variety of delivery systems for cargoes such as drugs and genes that can address many problems within the arteries. In order to improve the performance of current stents, nanotechnology provides different nanomaterial coatings, in addition to controlled-release nanocarriers, to prevent in-stent restenosis. Nanotechnology can increase the efficiency of drugs, improve local and systematic delivery to atherosclerotic plaques and reduce the inflammatory or angiogenic response after intravascular intervention. Nanocarriers have potential for delivery of imaging and diagnostic agents to precisely targeted destinations. This review paper will cover the current applications and future outlook of nanotechnology, as well as the main diagnostic methods, in the treatment of CAD.